Association of Tubotympanic Type Chronic Suppurative Otitis Media with Sinonasal Pathologies - Wasim Sajjad; Muhammad Zubair Khan; Muhammad Saleem Khan; Muhammad Aimen Ikram; RahmatUllah Khan; Furqan Ijaz (Pakistan Journal of Medicine and Dentistry)
Background: Sino-nasal and paranasal pathologies has a negative impact on the progression and treatment outcomes of chronic suppurative otitis media. The objective of this study is to find the association of chronic suppurative otitis media of the tubo-tympanic type with diseases of the nose and the sinonasal system.